2019
DOI: 10.29303/profood.v5i1.91
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Modifikasi Crosslink Terhadap Karakteristik Tepung Ubi Jalar Saat Dipanaskan

Abstract: ABSTRACT Sweet potato is a plant that is easy to be cultivated and very potential to be processed into flour. But the quality is still low compared to other flour especially when heated. Because it is done to improve the quality especially when heated. Modification done crosslink using sodium tripolyphosphate reagent (STPP). The purpose of this study was to determine the effect of modified flour on flour characteristics when heated. Parameters used in this research are water absorption, Swelling Power, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Based on Duncan's test, 0.5% STPP concentration could significantly decrease the solubility of the materials. The result was consistent with Yustiawan et al (2019), stating that the modification of starch with 1% STPP decreased solubility from 46.6% to 40%. Phosphate groups tended to form cross-links, acting as bridges between starch molecules.…”
Section: Water Solubility Index Of Analog Ricesupporting
confidence: 90%
See 1 more Smart Citation
“…Based on Duncan's test, 0.5% STPP concentration could significantly decrease the solubility of the materials. The result was consistent with Yustiawan et al (2019), stating that the modification of starch with 1% STPP decreased solubility from 46.6% to 40%. Phosphate groups tended to form cross-links, acting as bridges between starch molecules.…”
Section: Water Solubility Index Of Analog Ricesupporting
confidence: 90%
“…The high amylopectin content in gaplek and tapioca flour, approximately 50%, could increase water absorption. The addition of phosphate, capable of improving porosity, could increase water absorption in starch granules (Yustiawan et al, 2019). The heating of materials with high water absorption can facilitate gelatinization.…”
Section: Water Absorption Of Analog Ricementioning
confidence: 99%
“…During extrusion, chemical reaction that happened on starch surfaces [12], became one of the factors that caused level penetration of the water. Moreover, the increasing amounts of phosphate in tiwul rice production could caused the declining of rice hardness, in which phosphate enhances the material porosity so the water will easier penetrate into it [13]. Table 3 showed that the increasing of STTP slightly increase the springiness, but it was relatively similar to native rice.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium Tripolyphosphate memiliki sifat polar yang dapat mempermudah air untuk masuk ke dalam granula pati (Breemer et al, 2020). Semakin banyak senyawa fosfat maka semakin banyak terjadinya ikatan silang pati fosfat dan semakin banyak air yang terpenetrasi ke dalam granula pati tersebut (Yustiawan et al, 2019). Dengan menggunakan STPP akan mengakibatkan semakin tingginya tingkat gelatinisasi (Yustiawan et al, 2019).…”
Section: Aunclassified